Pathways to Attaining a Food Secure Philippines through a Competitive and Climate-Resilient Agri-Fisheries Sector (Posters) - Vidallo, Rene R.; Bayot, Ruvicyn S.; Monville-Oro, Emilita; Gonsalves, Julian Francis; Ilaga, Alicia; Sebastian, Leocadio S.; Manalo, U-Nichols; Baltazar, Perla (2020)
This set of posters, developed for the Climate Change Consciousness Week, highlights the key messages drawn from climate adaptation efforts and events done with Philippines’ Department of Agriculture-Regional Field Offices (DA-RFOs) across the country. This is a synthesis of lessons from the Adaptation and Mitigation Initiative in Agriculture (AMIA) village experience as a bankable model for establishing context specific, local adaptation platforms for developing and disseminating CRA technologies and processes.